2005
DOI: 10.1097/00126334-200501010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Gender Disparities in Receipt of Highly Active Antiretroviral Therapy Persist in a Multistate Sample of HIV Patients in 2001

Abstract: Although the overall prevalence of HAART has increased since the mid-1990s, demographic disparities in HAART receipt persist. Our results support attempts to increase access to care and frequency of outpatient visits for underutilizing groups as well as increased efforts to reduce persistent disparities in women, African Americans, and injection drug users (IDUs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
163
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 253 publications
(190 citation statements)
references
References 40 publications
20
163
0
4
Order By: Relevance
“…10,63 While most US cohorts have shown a steady decline in acute care usage as ART regimens improve and people initiate treatment with higher CD4 counts, 5 the ongoing high rate of acute care utilization in our study highlights that marginalized HIV-infected populations have not realized the same gains in overall health as the general HIVinfected population in the US. 8,64 While we found that mild/moderate food insecurity was associated with increased outpatient care, severe food insecurity had a non-significant relationship with the same outcome. This finding is consistent with previous studies indicating mixed results.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…10,63 While most US cohorts have shown a steady decline in acute care usage as ART regimens improve and people initiate treatment with higher CD4 counts, 5 the ongoing high rate of acute care utilization in our study highlights that marginalized HIV-infected populations have not realized the same gains in overall health as the general HIVinfected population in the US. 8,64 While we found that mild/moderate food insecurity was associated with increased outpatient care, severe food insecurity had a non-significant relationship with the same outcome. This finding is consistent with previous studies indicating mixed results.…”
Section: Discussionmentioning
confidence: 50%
“…[3][4][5] Gains in health, longevity, and reductions in acute care usage, however, have not been uniform across all population groups in the US. Among HIV-infected individuals, women, 6-9 injection drug users, 7,8,10 and racial/ethnic minorities 8,11,12 account disproportionately for morbidity and suboptimal health-care utilization patterns. Socioeconomic marginalization, in the form of unmet subsistence needs, may drive the acute care usage seen in these subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…Sites abstract specified data elements from patients' medical records; abstracted data are assembled into a uniform database. 20,21 The participating 14 sites treating adult patients are located in the Eastern (6), Midwestern (3), Southern (2), and Western United States (3). Seven of the sites have academic affiliations; 7 are community-based.…”
Section: Sitesmentioning
confidence: 99%
“…Throughout the HIV epidemic in the US, women, African Americans, and those with injection drug use histories are less likely to receive antiretroviral therapy (ART) for HIV disease, despite equivalent treatment indications [1][2][3][4] . Although there is evidence that these disparities are narrowing over time [5][6][7] , they have not been eliminated.…”
Section: Introductionmentioning
confidence: 99%